Effect of MoS2 on phenol decomposition in water after high-voltage pulse discharge treatment. (May 2022) - Wu, Haixia; Liu, Ruoyu; Sun, Yongjun; Wen, Yiyun; Zhao, Quanfa; Lin, Shaohua; Wang, Yong
Abstract: Molybdenum disulfide (MoS2 ) was added to the system after being treated with high-voltage pulse discharge plasma to improve the degradation efficiency of pollutants and reduce energy consumption. The discharge plasma-treated solution contains hydrogen peroxide and metal iron ions, and MoS2 addition can cause co-catalytic Fenton reaction. The effects of discharge time, initial pH, phenol concentration, MoS2 dosage, discharge voltage, and gas type on phenol removal and aqueous H2 O2 concentration were mainly investigated. Results showed that the addition of MoS2 after plasma treatment can reduce the plasma treatment time by 70% and maintain or even increase the degradation efficiency of phenol from 40% (after 20 min of discharge plasma) to 92% (after turning off the discharge and dosing with MoS2 for 30 min). Acidic conditions (pH = 3–4) and oxygen were beneficial to phenol removal. MoS2 addition greatly improved the catalytic oxidation of discharge plasma. This study provides a promising direction for water treatment based on plasma technology. Graphical abstract: Image 1 Highlights: MoS2 was used to improve phenol removal after high-voltage pulse plasma process. MoS2 addition after plasma can significantly save the electrical energy consumed by discharge. The catalysis was mainly the effect of MoS2 on the Fenton reaction.